(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The scientific significance of the study lies in the comparative assessment of clinical, functional and other methods of studying miners, in establishing a cause-and-effect relationship between morbidity rates and exposure to industrial vibration. The dependence of neurological disorders and metabolic changes in the body on the effects of vibration has been established, taking into account the level of vibration. The practical significance of the work is due to the determination of the degree of biochemical changes in the nervous system when the body is exposed to vibration, as well as the development of sensitive, informative biochemical tests for the early diagnosis of vibration disease and methods of prevention and treatment. The data obtained provide justification for the use of specific means of preventing nervous system disorders in vibration disease through the use of traditional medicine methods.